Monopol patentowy na produkty lecznicze - Niklewicz-Pijaczyńska, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Discussions concerning patenting of pharmaceutical products require aparticularly careful selection of postulates as they affect the fundamental area of human functioning — the issue of health and life. Both supporters of maintaining exclusive rights and their adversaries, therefore, reach for arguments that justify the validity of their position. These arguments are very diverse, but both sides of the on-going debate mention primarily those of an economic and legal nature. The first of these are related to emphasizing the amount of necessary financial effort and the need to motivate entities to undertake research. Postulates of the second type point to the possibility of applying exceptions to generally applicable regulations. The purpose of the publication is to picture arguments of one of the parties — those that sanction the maintenance of existing solutions within the scope of exclusive rights for pharmaceutical products. The research method is acritical analysis of the source literature in the fields of economics and law as well as jurisprudence study of cases. The conclusions point to the need for further, compatible problem-taking, both on the literature level and through specific solutions of jurisprudence practice, without which a consensus seems impossible.
Keywords: patents; innovations; monopoly; medicinal products; pharmacy